Injectable Stem Cell‐Laden Photocrosslinkable Microspheres Fabricated Using Microfluidics for Rapid Generation of Osteogenic Tissue Constructs. (16th February 2016) - Zhao, Xin; Liu, Shen; Yildirimer, Lara; Zhao, Hong; Ding, Ruihua; Wang, Huanan; Cui, Wenguo; Weitz, David
Abstract : Direct injection is a minimally invasive method of stem cell transplantation for numerous injuries and diseases. However, despite its promising potential, its clinical translation is difficult due to the low cell retention and engraftment after injection. With high versatility, high‐resolution control and injectability, microfabrication of stem‐cell laden biomedical hydrogels holds great potential as minimally invasive technology. Herein, a strategy of microfluidics‐assisted technology entrapping bone marrow‐derived mesenchymal stem cells (BMSCs) and growth factors in photocrosslinkable gelatin (GelMA) microspheres to ultimately generate injectable osteogenic tissue constructs is presented. Additionally, it is demonstrated that the GelMA microspheres can sustain stem cell viability, support cell spreading inside the microspheres and migration from the interior to the surface as well as enhance cell proliferation. This finding shows that encapsulated cells have the potential to directly and actively participate in the regeneration process. Furthermore, it is found that BMSCs encapsulated in GelMA microspheres show enhanced osteogenesis in vitro and in vivo, associated with a significant increase in mineralization. In short, the proposed strategy can be utilized to facilitate bone regeneration with minimum invasiveness, and can potentially be applied along with other matrices for extended applications. Abstract : A microfluidics‐assisted strategy for entrapping bone marrow‐derived mesenchymal stem cells (BMSCs) and growth factors in photocrosslinkable gelatin microspheres which can sustain BMSC viability, support cell spreading inside the microspheres and migration to the microsphere surface, and enhance osteogenesis both in vitro and in vivo, is presented. The proposed approach can be utilized to facilitate bone regeneration with minimum invasiveness.